2020
DOI: 10.3390/su12083426
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Potato Tuber Exposure to UV-C Radiation and Semi-Product Soaking in Water on Acrylamide Content in French Fries Dry Matter

Abstract: This study aims to determine the effect of raw potato tubers’ exposure to UV-C radiation and semi-products soaking in water on the content of acrylamide in the dry matter of French fries. The French fries were prepared from tubers of the Innovator variety of potato (Solanum tuberosum L.). Acrylamide contents were determined by HPLC-UV/Vis on a C-18 column after extraction of fried potatoes with acetonitrile. Potato tubers exposure to UV-C radiation caused an increase in acrylamide content and the soaking of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…As it can be seen, regardless of the applied UV-C treatment the content of sugars (Table 1) and acrylamide (Table 2) was always below the assumed limits which according to ECR 2017/2158 for acrylamide is 750 µg kg −1 FW, noting that the values expressed as DW are about three-fold higher than those expressed as FW. Similar increase in acrylamide level was observed by Sobol et al [18] in fried potatoes produced from irradiated potato tubers.…”
Section: Acrylamide Analysissupporting
confidence: 87%
See 1 more Smart Citation
“…As it can be seen, regardless of the applied UV-C treatment the content of sugars (Table 1) and acrylamide (Table 2) was always below the assumed limits which according to ECR 2017/2158 for acrylamide is 750 µg kg −1 FW, noting that the values expressed as DW are about three-fold higher than those expressed as FW. Similar increase in acrylamide level was observed by Sobol et al [18] in fried potatoes produced from irradiated potato tubers.…”
Section: Acrylamide Analysissupporting
confidence: 87%
“…An alleviated accumulation of reducing sugars (fructose and glucose) was observed during low-temperature storage of irradiated tubers [15], which consequently can lead to a decreased ability of acrylamide formation. However, a recent study showed that UV-C irradiation of potato tubers two days before the preparation of semi-finished products can increase the acrylamide content in fried potatoes, although the content of sugars in tubers was not analyzed in this study [18]. Reducing sugars, along with free amino acid asparagine, are the precursors in Maillard's reactions in which acrylamide is formed in potatoes fried at temperatures above 120 • C [19].…”
Section: Introductionmentioning
confidence: 75%
“…The color of fried potato products is an important organoleptic characteristic decisive for product quality and positively correlated with the acrylamide content. The darker the color, the higher the concentration of this compound [6][7][8][9][10][11][12][13][14]. Therefore, French fry color is a reliable indicator of safety of this food product.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the applica-tion of short-wavelength radiation is significantly reliant on the dosage administered and can result in altered characteristics of the product during the exposure (Lemessa et al, 2022). Within this context, an interesting finding was declared by Sobol et al (2020). The most significant reduction in acrylamide levels was observed in French fries made from semi-processed potatoes that had been soaked in water.…”
Section: Uv and Gamma Irradiation Techniquesmentioning
confidence: 99%